MARINE WOOD BORER NUTRIENTS FROM MANGROVE FOREST OF WEST KALIMANTAN INDONESIA FOR NEW FOOD SOURCES - Farah, Diba; Bayu, Wanamukti; Ros, Miati; Gusti, Eva Tavita; Khairul Adha, Bin Abdul Rahim; Ann, Chen Cheng (AID Conference, 2021)
Marine wood borer is one of wood destroying organisms which found in mangrove forests. They have an important function as bio-indicators on environment. The purpose of this research is to analysis the nutritional content of fresh marine wood borer and flour from marine wood borer. The method used consists of the inventory of marine wood borer at the Polaria mangrove forest, Mempawah Regency West Kalimantan Indonesia, and analysis of fresh marine borer nutritional content and marine borer flour. The analysis included of moisture content, ash content, protein, fat and carbohydrate which was carried out by proximate analysis method. The results showed that fresh marine wood borer weight was 780 gr. The yield of marine wood borer meat preparation was 88.46%. The average value of proximate analysis of fresh marine wood borer consist of moisture content was 13.58%, fat content was 3.90%, protein content was 10.60%, ash content was 16.17% and carbohydrate content was 55.75%. Meanwhile on marine wood borer flour obtained the moisture content was 4.57%, fat content was 6.28%, protein content was 40.65%, ash content was 26.54% and carbohydrate content was 21.96%. Analysis proximate showed that fresh marine wood borer obtained the higher results compared to the marine wood borer flour. This value includes the moisture content, and carbohydrates content. Nutrients analysis showed that marine wood borer has a potential to become a source for a food for human.